Monitoramento metacognitivo em adultos analfabetos funcionais e absolutos - Fujie, Márcia Akemi (Universidade Federal de São Carlos, 2017)
Self-regulation refers to thoughts, feelings and actions that are planned and cyclically adapted so as to make the individual reach their goals. Within the self-regulation is the metacognitive monitoring, the ability with which the individual follows and evaluates their own cognition. The present study was divided into two studies, both aimed to investigate the metacognitive monitoring of illiterate adults using the metacognitive judgement, a measure of the metacognitive monitoring, in cognitive tasks that evaluate the general factor of intelligence, processing speed and short-term memory. The relation between the real performance and the estimated performance was also investigated, including in which cognitive task the real performance related more to the estimated performance. In addition, we investigated which type of judgment model – the only difference between the two studies – was the most accurate. The participants of Study (1) included 34 functional or fully illiterate adults, from both genders, and age between 40 and 60 years old; and participants of Study (2) included 15 functional or fully illiterate adults, from both genders, and age between 20 and 74 years old. The instruments utilized were: Initial Interview, R-1 Test and subtests Digit Symbol-Coding, Symbol Search and Digit Span from the Wechsler Adult Intelligence Scale III (WAIS III), Judgment Register from 0 to 10, Judgement Register from 0 to 100 and Judgement Register with the use of a metric object. Results indicated that the real performance of the subjects, in both studies, were lower when compared to subjects with a greater level of education, and, according to the Pearson product-moment correlation coefficient, there was a significant correlation between the real performance and the estimated performance in the subtest Digit Symbol-Coding in Study 1, and significant correlation between real and estimated performance in the subtests Digit Symbol-Coding, Digit Span and Symbol Search in Study 2. In addition, results indicated that the judgment made with a metric object presented he most accurate measures.
Metacognitive monitoring in functional and fully illiterate adults
Keywords: Metacognição; Monitoramento metacognitivo; Analfabetos; Metacognition; Metacognitive monitoring; Illiterates; CIENCIAS HUMANAS::PSICOLOGIA